Shona proverbial lore, agency and optimism - Tembo, Charles (2016)
This article derives from, and is predicated on idea that Shona proverbs are a medium through which cultural agency and optimism are expressed. The article argues that agency and optimism as enshrined in Shona proverbs are crucial to the present as well as the future, especially in the context of challenges bedevilling Africa today such as HIV/AIDS, hunger, war among many others. The argument pursued in this article is that Shona proverbial lore is a cultural site, which reveals that optimism and agency are important to African people's experiential exigencies. The article maintains that contrary to Eurocentric conceptualizations of Africa and Africans which border on objectification, Shona proverbial lore provides ample and indisputable evidence that "optimism fulfils an important function within marriages, partnerships, family life and social relationship in general,” Bennett (2011:10). Furthermore, the article maintains that Shona people have a philosophy of life in which subjecthood, struggle and optimism are held sacred. In fact, proverbs reveal that "optimism of everyday life" Bennett (2011) performs crucial psychological, social and cultural functions in Shona society. The article posits that Shona proverbial lore is a lens through which the Shona people's philosophy of life, which is premised on agency, and the necessity of optimistic struggle are expressed. This article argues that Shona proverbial lore is a spring of hope for the Shona people as they grapple with life challenges of the present as well as the future. Guided and oriented by Afrocentricity, the article posits that Shona proverbs provide evidence that agency, transcendence and profound optimism are inevitable to life processes.